An integrated study of metabolomics and transcriptomics to reveal the anti-primary dysmenorrhea mechanism of Akebiae Fructus. (24th April 2021) - Ma, Baolian; Yang, Shilin; Tan, Ting; Li, Junmao; Zhang, Xiaoyong; Ouyang, Hui; He, Mingzhen; Feng, Yulin
Abstract: Ethnopharmacological relevance: Akebiae Fructus, a Tujia minority folk medicine and a well-known traditional Chinese medicine for soothing the liver, regulating Qi, promoting blood circulation and relieving pain, is widely used in the treatment of primary dysmenorrhea. However, little is known about its underlying mechanism. Aim of the study: To explore the effect of Akebiae Fructus on primary dysmenorrhea model induced by estradiol benzoate and oxytocin, and to provide better understanding of the mechanism of Akebiae Fructus for primary dysmenorrhea treatment. Materials and methods: The primary dysmenorrhea mouse model was used in this study. Except for the control group and the normal administration group, the mice of other groups were subcutaneously injected with estradiol benzoate (10 mg/kg/d) for 10 consecutive days. From the 5th day of the ten-day model period, the positive control groups were given 0.075 g/kg ibuprofen and 7.5 g/kg Leonurus granule, the drug groups were given 0.2 g/kg, 0.4 g/kg, 0.8 g/kg Akebiae Fructus extract, the normal administration group was given 0.8 g/kg Akebiae Fructus extract, and the same volume saline was given in the control group. On the tenth day, oxytocin (10 U/kg) was peritoneally injected after estradiol benzoate injected 1 h. After the oxytocin injection, writhing behavior was observed for 30 min. Then the uterine tissue was collected to measure the level of PGF2α and PGE2, and for histological analysis and transcriptomics analysis. Meanwhile, plasma and urine samples were collected for metabolomic analysis. Results: Akebiae Fructus inhibited the writhing, decreased the PGF2α level and ameliorated the morphological changes. 32 potential metabolic biomarkers in plasma and 17 in urine were found for primary dysmenorrhea, and after Akebiae Fructus treatment, 25 metabolites in plasma and 14 in urine were restored. These altered metabolites were mainly involved in lipid, amino acid and organic acid metabolism. For the transcriptomic study, a total of 2244 differentially expressed genes (1346 up-regulated and 898 down-regulated) were obtained between the control and model group, and 148 differentially expressed genes (DEGs) were found related with Akebiae Fructus treatment of primary dysmenorrhea. Correlation analysis was carried out based on the transcriptomic and metabolomic data. 5 differentially expressed genes (Plpp3, Sgpp2, Arg1, Adcy8, Ak5) were found related with the enrichment metabolic pathways. The mechanism by which Akebiae Fructus ameliorates primary dysmenorrhea may account for the regulation of the gene expression to control the key enzymes in the sphingolipid metabolism, arginine and proline metabolism, glycerophospholipid metabolism and purine metabolism, inhibiting the abnormal secretion of PGF2α, alleviating the uterine contraction and reducing inflammation and pain. Conclusions: Akebiae Fructus could effectively alleviate the symptoms of primary dysmenorrhea, regulate metabolic disorders, and control the related gene expression in primary dysmenorrhea. The study may provide clues for further study of Akebiae Fructus treatment on primary dysmenorrhea. Graphical abstract: Image 1 Highlights: The mechanism of Akebiae Fructus on primary dysmenorrhea was first studied by integrating metabolomics and transcriptomics. Akebiae Fructus had an ameliorative effect on primary dysmenorrhea. The metabolites (25 in plasma and 14 in urine) and 148 genes were modulated after Akebiae Fructus treatment. 5 differentially expressed genes were found related with the regulation of metabolic pathways.